2015
DOI: 10.1007/s00299-015-1767-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of secondary messengers and small organic molecules in auxin perception and signaling

Abstract: Auxin is a major phytohormone involved in most aspects of plant growth and development. Generally, auxin is perceived by three distinct receptors: TRANSPORT INHIBITOR RESISTANT1-Auxin/INDOLE ACETIC ACID, S-Phase Kinase-Associated Protein 2A and AUXIN-BINDING PROTEIN1. The auxin perception is regulated by a variety of secondary messenger molecules, including nitric oxide, reactive oxygen species, calcium, cyclic GMP, cyclic AMP, inositol triphosphate, diacylglycerol and by physiological pH. In addition, some sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…A model to explain some of the actions of melatonin in its role an as auxin-like regulator has recently been proposed (Arnao and Hernández-Ruiz, 2017a). The signalling molecule nitric oxide (NO), which is involved in a variety of physiological processes during plant growth and development and is an important modulator of stress responses and pathophysiological processes, seems to be a key player in this respect (Di et al, 2015;Hussain et al, 2016). NO has been extensively reported to regulate auxin responses in roots, adventitious roots, lateral roots, root hair formation and root gravitropism (Pagnussat et al, 2002;Correa-Aragunde et al, 2004;Hu et al, 2005;Lombardo et al, 2006).…”
Section: Melatonin and Auxin: Role In Growth Rhizogenesis And Tropismmentioning
confidence: 99%
“…A model to explain some of the actions of melatonin in its role an as auxin-like regulator has recently been proposed (Arnao and Hernández-Ruiz, 2017a). The signalling molecule nitric oxide (NO), which is involved in a variety of physiological processes during plant growth and development and is an important modulator of stress responses and pathophysiological processes, seems to be a key player in this respect (Di et al, 2015;Hussain et al, 2016). NO has been extensively reported to regulate auxin responses in roots, adventitious roots, lateral roots, root hair formation and root gravitropism (Pagnussat et al, 2002;Correa-Aragunde et al, 2004;Hu et al, 2005;Lombardo et al, 2006).…”
Section: Melatonin and Auxin: Role In Growth Rhizogenesis And Tropismmentioning
confidence: 99%
“…ARF genes are expressed in dynamic and differential patterning during development, and genetic studies have shown that individual ARFs control distinct developmental processes (Rademacher et al, 2012 ). Members of the ARF family of proteins contain domains associated with DNA binding, transcriptional activation or repression, and protein-protein interactions during auxin perception and signaling processes (Guilfoyle and Hagen, 2007 ; Di et al, 2015a ). Recently, the ARF gene family has been also investigated in several plants based on the recent release of the genome such as citrus, Medicago truncatula and Gossypium raimondii using both bioinformatics and molecular analyses (Li et al, 2015 ; Shen et al, 2015a ; Sun et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 1-Nnaphthylphthalamic acid (NPA) specifically inhibits PIN and ABCB cellular auxin transporters (Kleine-Vehn et al, 2006;Petrásek et al, 2006;Sauer et al, 2006;Blakeslee et al, 2007). On the other hand, PCIB is a putative auxin signaling inhibitor that has been reported to reduce polar auxin transport in diverse species by competing for auxin binding sites (Rose and Bopp, 1983;Oono et al, 2003;Hayashi et al, 2008;Belz and Piepho, 2013;Di et al, 2015). PCIB strongly inhibits auxin transport, probably because auxin signaling is required to promote PIN auxin transport (Sauer et al, 2006).…”
mentioning
confidence: 99%